Cell Transport Prompts the Performance of Low-Voltage Electroporation for Cell Inactivation. Issue 1 (December 2018) - Huo, Zheng-Yang; Li, Guo-Qiang; Yu, Tong; Feng, Chao; Lu, Yun; Wu, Yin-Hu; Yu, Cecilia; Xie, Xing; Hu, Hong-Ying
Abstract The inactivation of pathogens in liquids has broad applications, ranging from water disinfection to food pasteurization. However, common cell inactivation methods (e.g ., chlorination, ultraviolet radiation and thermal treatment) have significant drawbacks such as carcinogenic byproduct formation, energy intensiveness and/or nutrient structure destruction. Here, we fabricated a new approach to address these challenges by applying a low-voltage electroporation disinfection cell (EDC) and investigate the critical mechanisms of cell transport to allow high inactivation performance. The EDC prototypes were equipped with two one-dimensional (1D) nanostructure-assisted electrodes that enabled high electric field strength (>107 V m−1 ) near the electrode surface with a low applied voltage (1 V). We have identified that during electroporation disinfection, electrophoresis, dielectrophoresis and hydraulic flow are the three major mechanisms which transport cells into the vicinity of the electrode surface to achieve superior disinfection performance. The EDC treated 70 ml of bacteria sample with an initial cell concentration of 107 CFU ml−1 and achieved complete bacteria inactivation (survival rate <0.00001%; no live bacteria detected). Our findings will help to establish a foundation for the future development and implementation of low-voltage electroporation for cell inactivation.